Improvement in fetal pulmonary hypertension and maturity after reversal of ductal constriction: prospective cohort study. (1st September 2021) - Zielinsky, P.; MagalhÃes, G. A.; Zurita‐Peralta, J.; Sosa‐OlavarrÍa, A.; Marinho, G.; Van Der Sand, L.; Sulis, N. M.; Nicoloso, L. H.; Piccoli Jr, A.; Vian, I.
ABSTRACT: Objectives: To test the hypotheses that estimated mean pulmonary arterial pressure (MPAP) decreases and pulmonary vascular maturation, assessed by the ratio of pulmonary arterial flow acceleration time to ejection time (AT/ET ratio), increases after reversal of fetal ductus arteriosus constriction by reducing maternal intake of the causal agent (prostaglandin inhibitors, such as polyphenol‐rich foods or non‐steroidal anti‐inflammatory drugs), and that these effects are independent of gestational age, which are inferences not yet demonstrated in the clinical setting. Methods: This was a prospective cohort study comparing Doppler echocardiographic ductal flow dynamics, MPAP and pulmonary arterial flow AT/ET ratio in third‐trimester fetuses (≥ 28 weeks' gestation) with ductus arteriosus constriction, at the time of diagnosis and after 2 weeks of reduced maternal intake of prostaglandin inhibitors either by suspending the use of pharmacological agents with potential for prostaglandin inhibition or by restricting the consumption of polyphenol‐rich foods. MPAP was estimated using the Dabestani equation (MPAP = 90 − (0.62 × AT)), and pulmonary vascular maturity was assessed using the AT/ET ratio, according to reported validation studies. Student's t ‐test was used for comparison of variables at diagnosis with those after reversal of ductal constriction. Change in MPAP and pulmonary AT/ET ratio between the two assessments was compared with the expected change in the same gestational period in normal fetuses based on reference curves of MPAP and pulmonary AT/ET ratio constructed in normal fetuses from healthy pregnant women at 19–37 weeks' gestation, encompassing the same gestational age range as the study group (28–37 weeks). Results: Seventy pregnancies with fetal ductus arteriosus constriction were included in the study. After 2 weeks of reduced maternal intake of prostaglandin inhibitors, normalization of mean systolic (change from 1.86 ± 0.34 m/s at diagnosis to 1.38 ± 0.41 m/s; P < 0.001) and diastolic (change from 0.41 ± 0.11 m/s to 0.21 ± 0.065 m/s; P < 0.001) ductal velocities and of mean pulsatility index (change from 1.99 ± 0.20 to 2.55 ± 0.42; P < 0.001) was demonstrated. MPAP decreased between the assessments (change from 66.7 ± 6.90 mmHg at diagnosis to 54.5 ± 6.70 mmHg after 2 weeks; P < 0.001) and mean pulmonary AT/ET ratio increased (change from 0.20 ± 0.06 to 0.33 ± 0.07; P < 0.001). Change in MPAP between diagnosis and after 2 weeks of reduced maternal intake of prostaglandin inhibitors was −12.2 ± 0.30 mmHg, which was 5.3‐times higher than that in 305 normal fetuses over 2 weeks during the same gestational period (−2.3 ± 0.19 mmHg) ( P < 0.001), and change in pulmonary AT/ET ratio between the two assessments was 0.13 ± 0.08, which was 8.7‐times higher than that in normal fetuses in the same gestational period (0.015 ± 0.08) ( P < 0.001). Conclusions: Resolution of fetal ductal constriction is followed by a fall in MPAP and by an increase in pulmonary vascular maturity, to a significantly greater degree than is observed in normal fetuses in the same gestational‐age period. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.